Modelling soil water dynamics and root water uptake for apple trees under water storage pit irrigation - Guo, Xianghong; Lei, Tao; Sun, Xihuan; Ma, Juanjuan; Zheng, Lijian; Zhang, Shaowen; He, Qiqi (International Journal of Agricultural and Biological Engineering, 2019)
Water storage pit irrigation is a new method suitable for apple trees. It comes with advantages such as water saving, water retention and drought resistance. A precise study of soil water movement and root water uptake is essential to analyse and show the advantages of the method. In this study, a mathematical model (WSPI-WR model) for 3D soil water movement and root water uptake under water storage pit irrigation was established based on soil water dynamics and soil moisture and root distributions. Moreover, this model also considers the soil evaporation, pit wall evaporation and water level variation in the pit. The finite element method was used to solve the model, and the law of mass conservation was used to analyse the water level variation. The model was validated by experimental data of the sap flow of apple trees and soil moisture in the orchard. Results showed that the WSPI-WR model is highly accurate in simulating the root water uptake and soil water distributions. The WSPI-WR model can be used to simulate root water uptake and soil water movement under water storage pit irrigation. The simulation showed that orchard soil water content and root water uptake rate centers on the storage pit with an ellipsoid distribution. The maximum distribution region of soil water and root water uptake rate was near the bottom of the pit. Distribution can reduce soil evaporation in the orchard and improve the soil water use efficiency in the middle-deep soil.Keywords: root water uptake, soil water dynamics, numerical simulation, water storage pit irrigation, apple treeDOI: 10.25165/j.ijabe.20191205.4005Citation: Guo X H, Lei T, Sun X H, Ma J J, Zheng L J, Zhang S W, et al. Modelling soil water dynamics and root water uptake for apple trees under water storage pit irrigation. Int J Agric & Biol Eng, 2019; 12(5): 126–134.